Electrical characterization of ITO/PEDOT-PSS/MEH-PPV:PCBM organic diode - Yakuphanoğlu, Fahrettin; Farooq, W. A. (Natl Inst Optoelectronics, 2011)
The electrical characterization of organic diode with a configuration ITO/poly [2-methoxy-5-(2-ethyl)hexoxy-1,4-phenylenevinylene]:[6,6]-phenyl C-61-butyric acid methyl ester blend was analyzed by current-voltage and capacitance-voltage methods. The junction parameters of the diode were calculated from the current-voltage and capacitance-voltage data and are discussed. The ideality factor n and barrier height phi(b) values of the diode were found to be 3.06 and 0.96 eV, respectively. The diode shows a non-ideal current-voltage behavior due to a high probability of electrons and holes recombining in the depletion region or series resistance and by the presence of an interfacial layer.
Keywords: Organic semiconductors; Diode; Electrical properties